Electrostatic Comb-Drive Actuator with High In-Plane Translational Velocity - Yomna M. Eltagoury; Mostafa Soliman; Yasser M. Sabry; Mohammed J. Alotaibi; Diaa Khalil (Micromachines, 2016)
This work reports the design and opto-mechanical characterization of high velocity comb-drive actuators producing in-plane motion and fabricated using the technology of deep reactive ion etching (DRIE) of silicon-on-insulator (SOI) substrate. The actuators drive vertical mirrors acting on optical beams propagating in-plane with respect to the substrate. The actuator-mirror device is a fabrication on an SOI wafer with 80 μm etching depth, surface roughness of about 15 nm peak to valley and etching verticality that is better than 0.1 degree. The travel range of the actuators is extracted using an optical method based on optical cavity response and accounting for the diffraction effect. One design achieves a travel range of approximately 9.1 µm at a resonance frequency of approximately 26.1 kHz, while the second design achieves about 2 µm at 93.5 kHz. The two specific designs reported achieve peak velocities of about 1.48 and 1.18 m/s, respectively, which is the highest product of the travel range and frequency for an in-plane microelectromechanical system (MEMS) motion under atmospheric pressure, to the best of the authors’ knowledge. The first design possesses high spring linearity over its travel range with about 350 ppm change in the resonance frequency, while the second design achieves higher resonance frequency on the expense of linearity. The theoretical predications and the experimental results show good agreement.